Tinjauan Pustaka: Sindrom Metabolik - Debbi Anggraini (Syntax Corporation Indonesia, 2024)
Metabolic Syndrome reflects a series of metabolic disorders, involving hypertension, insulin resistance, obesity and dyslipidemia. The prevalence of metabolic syndrome varies greatly in proportion to the diversity of criteria in determining the diagnosis of this syndrome. The criteria for metabolic syndrome are created by several health organizations, such as WHO, IDF and NCEP:ATP III. Many studies agree that the percentage of metabolic syndrome reaches a quarter of the world's population. Several factors such as poor lifestyle, unbalanced diet, smoking, alcohol consumption, sleep disorders, stress, and genetics are risk factors for the development of pathogenesis of this syndrome. Among the many pathogenesis pathogenesis, insulin resistance, neurohormonal activation and chronic inflammation are three pathogenesis pathways that are often associated with metabolic syndrome. Target therapy in this case involves non-pharmacological fields in the form of lifestyle modification and consumption of foods that contain health effects (nutraceutical), as well as pharmacological in the form of specific drugs for conditions of hyperglycemia, obesity, dyslipidemia, antiplatelet and hypertension.